Unraveling the Evolutionary Tales of Yunnanopilia longistaminea (Opiliaceae): Insights from Genetic Diversity, Climate Adaptation, and Conservation Strategies - Guansong Yang; Liu Yang; Shikang Shen; Yuehua Wang; Yuying Wang (Plants)
The evolutionary history of Yunnanopilia longistaminea, a vulnerable plant endemic to the Yuanjiang-Honghe River Valley in southwestern China, was investigated using cpDNA and nrDNA sequences along with ecological niche modeling. Understanding the genetic diversity and population structure of Y. longistaminea is crucial for developing effective conservation strategies and managing its genetic resources. This study comprehensively sampled 295 individuals from 16 populations, which represent the species’ entire global distribution range, ensuring a thorough and representative analysis of its genetic diversity and population structure. The results revealed high genetic diversity and population structure, with significant genetic differentiation among populations. Specifically, the total nucleotide diversity was 2.40 × 10−3 for cpDNA and 1.51 × 10−3 for nrDNA, while the total haplotype diversity was 0.605 for cpDNA and 0.526 for nrDNA. The divergence time of ancestral haplotypes of Y. longistaminea was estimated to be around 2.19 million years ago based on nrDNA and 2.72 million years ago based on cpDNA. These divergence times are comparable to those of other ancient plant species, suggesting a long evolutionary history. The population size of Y. longistaminea was found to have significantly declined around 30,000 years ago. The current distribution model suggests that Y. longistaminea primarily inhabits the warm temperate zone of China, and the LGM distribution model predicts a concentration of the species in Yuanjiang-Honghe River Valley in southwestern China. This study concludes that the southwestern region of China may have served as a glacial refuge for Y. longistaminea. These findings suggest that establishing protected areas in these regions and creating gene banks for ex situ conservation could be effective strategies to preserve the genetic diversity of Y. longistaminea. Further research on its population dynamics and genetic adaptation to climate change is valuable for understanding the species’ evolutionary history and conservation.